Validação de método cromatográfico por exclusão molecular para avaliação de interferon-alfa2a e estudos de correlação - Zimmermann, Estevan Sonego (2010)
Human interferon-α2a (hIFN-α2a) is a natural protein produced by the cells of the immune system with antiviral, antiproliferative and immunomodulatory properties. A size exclusion liquid chromatography (SE-LC) method was validated for the determination of recombinant interferon-α2a (rhIFN-α2a) in pharmaceutical formulations without human serum albumin. The SE-LC method was carried out on a BioSep-SEC-S 2000 column (300 mm x 7.8 mm i.d.) maintained at 25°C. The mobile phase consisted of 0.001 M monobasic potassium phosphate, 0.008 M sodium phosphate dibasic and 0.2 M sodium chloride buffer, pH 7.4, run at a gradiente flow rate and using photodiode array (PDA) detection at 214 nm. The chromatographic separation was achieved with retention time of 17.2 min, and was linear over the concentration range of 0.5-50 MUI/mL (r2 = 0.9996). The accuracy was 101.39% with bias lower than 1.67%. The limits of detection and quantitation were 0.22 and 0.5 MIU/mL, respectively, and the method validation demonstrated acceptable results for precision and robustness. The proposed method was applied for the analysis of rhIFN-α2a in pharmaceutical dosage forms, and the content/potencies correlated to the previously validated reversed-phase (RP-LC), and the in vitro bioassay. The pharmaceutical samples were analyzed by the chromatographic methods and compared to the bioassay, showing mean differences between the estimated potency of 1.50% higher for SE-LC, and 2.45% lower for the RP-LC. The alternative methods studies contribute to improve the quality control, assuring the therapeutic efficacy of the biological medicine. Moreover, the pharmacokinetic parameters of the formulations A and B were evaluated by subcutaneous injection in rats, showing comparable profiles with Cmax of 7924.60 and 8698.68 pg/mL, respectively, and Tmax= 60 min.